Visual ethics a guide for photographers, journalists, and media makers - Lester, Paul Martin; Martin, Stephanie A. 1974-; Smith-Rodden, Martin
"An indispensable guide to visual ethics, this book addresses the need for critical thinking and ethical behavior among students and professionals responsible for a variety of mass media visual messages. Written for an ever-growing discipline, authors Paul Martin Lester, Stephanie A. Martin, and Martin Rodden-Smith give serious ethical consideration to the complex field of visual communication. The book covers the definitions and uses of six philosophies, analytical methods, cultural awareness, visual reporting, documentary, citizen journalists, advertising, public relations, typography, graphic design, data visualizations, cartoons, motion pictures, television, computers and the web, augmented and virtual reality, social media, the editing process, and the need for empathy. At the end of each chapter are case studies for further analysis and interviews with thoughtful practitioners in each field of study, including Steven Heller and Nigel Holmes. This second edition has also been fully revised and updated throughout to reflect on the impact of new and emerging technologies. This book is an important resource for students of photojournalism, photography, filmmaking, media and communication, and visual communication, as well as professionals working in these fields"--Provided by publisher.